Introduction to the diasporic autobiographical documentary. (1st June 2020) - Scafirimuto, Guglielmo
This article aims to introduce a new film genre that I call 'diasporic autobiographical documentary' that I have been working on during my last years of research, first in France and now in a broader context. In this genre, diasporic cinema and autobiographical documentary meet and create an original ensemble, especially produced in the last twenty years, in order to give place to the search for identity by individuals belonging to more than one nation and culture. In the first part, the present text exposes the principal axes of definition of this body of work, following Raphaëlle Moine's theory of film genre. In the second part, it deals with two concepts necessary to understand the main issues of this genre: the diasporic subject and the origin. In the search of their lost origin and of their collective memories, diasporic subjects negotiate their identity through the subjective enunciation of the documentary, and offer an important work of reflection on today transnationalism and multiculturalism.